Lifelong learning of property managers in enabling sustainable and energy efficient residential buildings: experiences of care project in Tampere region - Kalle Tammi; Pekka Väisälä; Petri Murtomaa; Jussi-Pekka Juvela; Jani Hietakangas; Timo Lähteenmäki; Silva Vuopponen (Acta Polytechnica CTU Proceedings)
The existing building stock causes 40% of the total energy consumption in the European Union. The high energy consumption together with ageing buildings put strong pressure on renovation of buildings and lowering of CO2 emissions. The Directives on Energy Performance of Buildings (EPBD) and Energy Efficiency (EED) were established to urge and steer the activities in the EU member countries. There are about 90,000 housing companies in Finland. They consist of 1,7 million apartments and 2,7 million residents, which makes housing companies a significant energy consumer. Around 50 % of the building stock in Finland was built between 1960s and 1980s. The average level of technical building systems is decent. Measures are still needed to tackle the increasing maintenance backlog and energy consumptionobjectives. Management of housing companies consists of the general meeting of apartment owners and a board elected by the general meeting. In addition, a vast majority of housing companies have a professional property manager whose role corresponds to CEO. The property manager’s expertise plays an essential role in planning and execution of maintenance and energy efficiency. The role of the property manager calls for multidisciplinary competencies and continuous learning. The CARE - Resource efficient caretaking of residential buildings project implemented flexible courses and training for property managers to enhance their technical understanding of energy efficient renovations and retrofit of new energy solutions.